Re-Examining Textual Information of the Word Halal from the Perspective of Naturally Occurring Data (NOD): [Memugar Maklumat Teks Kata Halal daripada Perspektif Naturally Occurring Data (Nod)] (Jurnal Bahasa, 2018)
This study aims to re-examine the description of the meaning of the word halal in Kamus Dewan (2016). The loanword, which originates from the Arabic halla, yahillu, hillan, wahalalan, is denoted with four descriptions in the Malay language dictionary. These descriptions, however, depict limited information when compared to the original word, which in turn may cause ambiguity. This study, which puts forth a real-world linguistic analysis based on the naturally occurring data (NOD) specifically discusses the textual information of the second meaning of the word halal in the dictionary, which defines it as "yang diperdapat, diperoleh, diperbuat". A total of 31 349 occurrences of the word halal, which were extrapolated from the DBP, DBP-UKM and WebCorp database, were analysed based on the semantic prosody theory. The theory, which stresses on the element of consistent aura, managed to further elaborate the textual information of the source definition (yang diperdapat, diperoleh, diperbuat) into four sub-definitions, which concern material, activities, sustenance and possession. This elaboration demonstrates that the NOD-based analysis is able to facilitate the comprehension of ambiguous words so that an inclusive understanding of the meaning can be achieved.Keywords: naturally accurring data, real-world linguistics, halal, meaning, WebCorp